2018
DOI: 10.3389/fncel.2018.00157
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Viral Vector Serotype DJ-Mediated Overexpression of N171-82Q-Mutant Huntingtin in the Striatum of Juvenile Mice Is a New Model for Huntington’s Disease

Abstract: Huntington’s disease (HD) is an autosomal-dominant inherited neurodegenerative disorder characterized by motor, psychiatric and cognitive symptoms. HD is caused by an expansion of CAG repeats in the huntingtin (HTT) gene in various areas of the brain including striatum. There are few suitable animal models to study the pathogenesis of HD and validate therapeutic strategies. Recombinant adeno-associated viral (AAV) vectors successfully transfer foreign genes to the brain of adult mammalians. In this article, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
4
8
0
Order By: Relevance
“…Our histology re-sults also showed microglia and astrocyte activation in AAV2-82Q-injected rats. This result is similar to the in vivo mouse HD model obtained by stereotaxic infection of AAV-DJ containing N171-82Q, which showed that the viral vector infects neurons, microglia, and astrocytes, but not oligodendrocytes 12) . Based on these results, we confirm the possibility of a new Huntington rat model produced by direct infection of AAV2-82Q into the striatum.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our histology re-sults also showed microglia and astrocyte activation in AAV2-82Q-injected rats. This result is similar to the in vivo mouse HD model obtained by stereotaxic infection of AAV-DJ containing N171-82Q, which showed that the viral vector infects neurons, microglia, and astrocytes, but not oligodendrocytes 12) . Based on these results, we confirm the possibility of a new Huntington rat model produced by direct infection of AAV2-82Q into the striatum.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, this virus has been inserted into both differentiated and undifferentiated cells and exists as an episomal vector, which allows long-term gene expression [ 5 , 18 ]. Jang et al [ 12 ] have been generated an HD mice model using AAV-DJ-N171-82Q mHTT. AAV-DJ and AAV2 have very strong tropism for neurons and fast expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…chemogenetics 20 ). AAVs have also been used to create animal models of CNS disorders by delivering pathogenic constructs to brain regions of interest, such as the overexpression of a-synuclein in the striatum that results in progressive neurodegeneration and motor phenotypes characteristic of Parkinson's disease [21][22][23] , or of expanded glutamine-encoding CAG repeats to create a striatal degeneration model of Huntington's disease (HD) 21,24,25 , or of amyloid beta to reproduce features of Alzheimer's disease 26,27 .…”
Section: Introductionmentioning
confidence: 99%